Tadeusz Stryjakiewicz Tomasz Kaczmarek Michał Męczyński Jerzy J. Parysek Krzysztof Stachowiak Policies and strategies in Poznan. How to enhance the city’s competitiveness. ACRE report 10.8 - Redakcja Czasopisma (Rozwój Regionalny i Polityka Regionalna)
Tadeusz Stryjakiewicz Tomasz Kaczmarek Michał Męczyński Jerzy J. Parysek Krzysztof Stachowiak Policies and strategies in Poznan. How to enhance the city’s competitiveness. ACRE report 10.8